2015
DOI: 10.1002/dc.23388
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial vaginosis and inflammatory response showed association with severity of cervical neoplasia in HPV‐positive women

Abstract: Vaginal infections may affect susceptibility to and clearance of human papillomavirus (HPV) infection and chronic inflammation has been linked to carcinogenesis. This study aimed to evaluate the association between bacterial vaginosis (BV) and inflammatory response (IR) with the severity of cervical neoplasia in HPV-infected women. HPV DNA was amplified using PGMY09/11 primers and genotyping was performed using a reverse line blot hybridization assay in 211 cervical samples from women submitted to excision of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 47 publications
1
19
0
Order By: Relevance
“…In addition, patients with persistent HPV infection showed a significantly higher prevalence of BV than patients with HPV clearance ( 129 ). Another study showed an association between cervical neoplasia (CIN2+) and the presence of BV (odds ratio: 3.90), providing additional support for the association between BV, HPV infection, and cervical cancer development ( 130 ).…”
Section: The Role Of Vaginal Microbiome Analysis In Hpv Diagnosis Andmentioning
confidence: 90%
“…In addition, patients with persistent HPV infection showed a significantly higher prevalence of BV than patients with HPV clearance ( 129 ). Another study showed an association between cervical neoplasia (CIN2+) and the presence of BV (odds ratio: 3.90), providing additional support for the association between BV, HPV infection, and cervical cancer development ( 130 ).…”
Section: The Role Of Vaginal Microbiome Analysis In Hpv Diagnosis Andmentioning
confidence: 90%
“…Reports have suggested that human papillomavirus (HPV), such as HPV 16 and 18, are well established as an etiological agent for CC and have the ability to transform normal cervical cells into neoplastic cells [2, 3]. However, infection with HPV by itself is thought to be insufficient for the malignant transformation of HPV infected normal cervical cells [4]. Recently, with the deepening research on CC, it has been confirmed that HPV infection along with persistent chronic inflammation can induce carcinogenesis [2, 4].…”
Section: Introductionmentioning
confidence: 99%
“…However, infection with HPV by itself is thought to be insufficient for the malignant transformation of HPV infected normal cervical cells [4]. Recently, with the deepening research on CC, it has been confirmed that HPV infection along with persistent chronic inflammation can induce carcinogenesis [2, 4]. …”
Section: Introductionmentioning
confidence: 99%
“…It is likely that these infections result in localized chronic inflammation that provides a suitable niche for persistent HPV infection ( Figure 5). A recent study evaluated association between bacterial vaginosis (BV) and inflammatory response (IR) with the severity of cervical neoplasia in HPVinfected women and have revealed vaginal infections irrespective of their nature (bacterial, fungal, yeast) increased the susceptibility, effects the clearance of HPV infection and eventually contributed towards HPVinduced cervical or genital carcinogenesis (38). These infections alter the microenvironment in the genital areas thereby causing severe inflammation, which en routes the development of cervical neoplasia.…”
Section: Spectrum Of Hpv-associated Diseases and Magnitude Of The Promentioning
confidence: 99%